ACL Injury, Return To Play And Reinjury In The Elite, Collegiate Athlete: An Analysis Of A Single, Division I NCAA Cohort. Issue 7 (29th July 2014) - Kamath, Ganesh V.; Murphy, Timothy; Creighton, Robert A.; Taft, Timothy N.; Spang, Jeffrey T.
Objectives: Graft survivorship, reinjury rates, and career length are poorly understood after ACL reconstruction in the elite, NCAA Division-I athlete. The purpose of this study was to examine the outcomes of ACL reconstruction in a Division-I athlete cohort. Methods: Retrospective chart review was performed of all Division-I athletes at a single, public university from 2000 to 2009 until completion of eligibility. Athletes with a Pre-collegiate (PC) and Intra-collegiate (IC) ACL reconstruction were separated into two cohorts. Graft survivorship, reoperation rates, and career length information was collected. Results: 35 athletes were identified with a pre-collegiate (PC) ACL reconstruction; 60 with an intra-collegiate (IC) reconstruction. The PC group had a 17.1% injury rate to the original graft, with a 20.0% rate of contralateral ACL injury. For the IC group, the reinjury rates were 1.9% to the ACL graft, with a 9.2% rate of contralateral ACL injury after an IntraCollegiate ACL reconstruction. The PC group used 78% of their total eligibility (avg 3.11 yrs). Athletes in the IC group used an average of 77% of their remaining NCAA eligibility. 88.3% of the IC group played an additional non-redshirt year after their injury. Reoperation rate for the PC group was 51.4% and 20.3% for the IC group. Conclusion: Reoperation and reinjury rates are high after ACL reconstruction in the Division-I athlete. Pre-collegiate ACL reconstruction is associated with a very high rate of repeat ACL reinjury to the graft or opposite knee (37.1%). The majority of athletes are able to return to play after successful reconstruction.